Genome sequence of Methylocystis hirsuta CSC1, a polyhydroxyalkanoate producing methanotroph - Sergio Bordel; Elisa Rodríguez; Raúl Muñoz (MicrobiologyOpen, 2019)
Abstract Polyhydroxyalkanoates (PHAs) are biodegradable plastics that can be produced by some methanotrophic organisms such as those of the genus Methylocystis. This allows the conversion of a detrimental greenhouse gas into an environmentally friendly high added‐value bioproduct. This study presents the genome sequence of Methylocystis hirsuta CSC1 (a high yield PHB producer). The genome comprises 4,213,043 bp in 4 contigs, with the largest contig being 3,776,027 bp long. Two of the other contigs are likely to correspond to large size plasmids. A total of 4,664 coding sequences were annotated, revealing a PHA production cluster, two distinct particulate methane monooxygenases with active catalytic sites, as well as a nitrogen fixation operon and a partial denitrification pathway.